1997
DOI: 10.1159/000129542
|View full text |Cite
|
Sign up to set email alerts
|

Blood Clearance of <sup>99m</sup>Tc-Trimethyl-Br-IDA Discriminates between Different Degrees of Severe Liver Ischaemia &ndash; Reperfusion Injury in the Rat

Abstract: The kinetics of 99mTc-Trimethyl-Br-IDA blood clearance was analysed in the rat 24 h after warm ischaemia and reperfusion of the liver. There were changes in the elimination of 99mTc-Trimethyl-Br-IDA depending on the length of the ischaemic period and the dose given. Statistically significant differences were found between the various periods of ischaemia when higher doses of the radionuclide were utilised. At lower doses, the clearance was not capable to discriminate between control rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…It was argued that elevation of serum enzymes indicates that membrane rupture and cell death had already occurred before the study at 1 wk, and it was assumed that if data had been collected at earlier times (2,4,6,24,48,72, or 96 h) after introduction of the diet, it could have been possible to show cell damage before death by demonstrating a normal uptake rate but a prolonged excretory half-life (22). This argument is supported by the previously documented unperturbed 99m Tc-hydroxyiminodiacetic acid uptake observed in chronic liver disease in a few studies (21)(22)(23)36). These studies used thiacetarsamide, CCl4, copper, and ischemia to induce liver damage; however, these changes are not representative of human NASH.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It was argued that elevation of serum enzymes indicates that membrane rupture and cell death had already occurred before the study at 1 wk, and it was assumed that if data had been collected at earlier times (2,4,6,24,48,72, or 96 h) after introduction of the diet, it could have been possible to show cell damage before death by demonstrating a normal uptake rate but a prolonged excretory half-life (22). This argument is supported by the previously documented unperturbed 99m Tc-hydroxyiminodiacetic acid uptake observed in chronic liver disease in a few studies (21)(22)(23)36). These studies used thiacetarsamide, CCl4, copper, and ischemia to induce liver damage; however, these changes are not representative of human NASH.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies in patients with acute and chronic parenchymal liver disease (5,20) have shown a correlation between hepatobiliary function assessed by 99m Tc-mebrofenin scintigraphy and the histopathologic severity of the underlying pathology (21)(22)(23). Therefore, HBS would be of great clinical importance for the follow-up of patients during pharmacologic therapy…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic extraction fraction and T 1/2 peak , measured by HBS, were used as a noninvasive method of evaluating hepatic function after ischemia-reperfusion injury to quantify the protective effect of new interventions on ischemia-reperfusion injury (81)(82)(83).…”
Section: Hbs In Experimental Surgical Researchmentioning
confidence: 99%
“…In this regard, mebrofenin -N- (3-bromo-2,4,6-trimethyl-acetanilide)iminodiacetic acid -and related compounds possess exclusive affinity for hepatocytes followed by transport into bile [3][4][5][6][7][8][9][10][11][12][13]. Although relevant hepatobiliary transporters have been well studied [14,15], gaps remain in critical areas and the identity of specific mebrofenin transporter(s) is unknown.…”
Section: Introductionmentioning
confidence: 99%